Three rootstocks and six spacings on "Valência" orange production - Koller, Otto Carlos; Barradas, Carlos I. N.; Lichtemberg, Luiz A.; Dornelles, Ana Lúcia C.; Merten, Gustavo H. (Pesquisa Agropecuaria Brasileira, 2014)
In this experiment the effects of the combination of two row widths with three plant spacings within row on the yield of 'Valência' Orange (Citrus sinesis (L.) Osbeck), grafted on three kinds of rootstocks: 'Rangpur' lime (Citrus limonia Osbeck) 'Caipira' orange (Citrus sinensis (L.) Osbeck), and 'Trifoliata' Orange (Poncirus trifoliata Raff.) were studied. The research was conducted at the Estação Experimental Agronômica da Universidade Federal do Rio Grande do Sul, from 1976 through 1981. The lowest spacings tested did not affect plant productivity, but they increased yield per area proportionately to the number of trees per area unit. The highest production per plant and the highest fruit weight were obtained by 'Rangpur' lime; 'Caipira' was the second. and ' Trifoliata' the third. In the first harvest, 'Trifoliata' induced higher productivity than the 'Caipira'; the opposite was observed on the second and third harvests. Also in the first harvest 'Valência' orange grafted on 'Rangpur' lime rootstocks produced higher yields per plant when these were spaced 2 m apart than by wider spacings.